GE_GERICHTE C/30704/2010 vom 27. September 2013 - GE Cour de justice (2013)
MANDAT; CONDITIONS GÉNÉRALES DU CONTRAT; RESPONSABILITÉ CONTRACTUELLE; ORDRE DE PAIEMENT; BANQUE | CC.8; CO.18; CO.84; CO.97.1; CO.99.3; CO.100.1; CO.101.3; CO.103; CO.104; CO.402; CPC.317.1; CPC.317.3; CPC.318.3